2020
DOI: 10.1016/j.jasc.2020.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Learning cytology in times of pandemic: an educational institutional experience with remote teaching

Abstract: Introduction As the coronavirus pandemic swept across national and state borders, institutions of higher learning, including cytology, began closing campuses and moving instruction online. We have described a method of remotely teaching cytology in our institution, including using the telecytology concept used with rapid onsite evaluation and remote conferencing and educational tools to conduct eCytology learning. This is a cost-effective method to transition a traditional in-classroom program into online teac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 17 publications
(17 reference statements)
0
15
0
4
Order By: Relevance
“…24 Chiou. 25 described a remote ecytology tool that they utilized at their institution at New Jersey, USA for teaching cytotechnology students. Their experience is based on the use of easy video teaching and communication platforms Zoom conferencing (San Jose, California) and Canvas (Salt Lake City, Utah) as their online tools for lectures, microscopy sessions, and tests.…”
Section: Covid-19 and Trainee Educationmentioning
confidence: 99%
“…24 Chiou. 25 described a remote ecytology tool that they utilized at their institution at New Jersey, USA for teaching cytotechnology students. Their experience is based on the use of easy video teaching and communication platforms Zoom conferencing (San Jose, California) and Canvas (Salt Lake City, Utah) as their online tools for lectures, microscopy sessions, and tests.…”
Section: Covid-19 and Trainee Educationmentioning
confidence: 99%
“…O que fazer com atividades que, à primeira vista, parecem inapelavelmente exigentes quanto à presencialidade (e, de fato, são exigentes), demarcando o processo de ensinoaprendizagem? No universo dos cursos da área da saúde, por exemplo, cresceram exponencialmente as publicações recentes, tratando do ensino virtual em áreas básicas, clínicas, cirúrgicas, estágios de campo, em praticamente todas as (sub) especialidades médicas 2,[31][32][33][34][35][36][37][38][39][40][41][42] . Houve até quem mostrasse reverência à virtualidade de cadáveres, em experiências de aulas com anatomia 43 .…”
Section: Há Alternativas? Presença Física Ou Holograma Digital (Metapresença) Nos Estágiosunclassified
“…COVID-19 pandemics produced changes in social interactions and social distancing intended on reducing these interactions amongst people, causing education institutions to adopt the emergency remote teaching format. In this national higher education context, a survey carried out by the College of Deans of Undergraduate Studies (COGRAD-2020), linked to the National Association of Directors in Federal Institutions of Higher Education (ANDIFES), demonstrated that most of the IFES (Federal Institutions of Higher Education), planned complementary academic calendars that were completely remote or hybrid (Aguilera-Hermida, 2020;Ali, 2020;Buttler et al, 2021a;Chiou, 2020;Sarah I Hofer et al, 2021;Secundo et al, 2021a).…”
Section: Introductionmentioning
confidence: 99%